Computational Modelling of Pisum Sativum L. Superoxide Dismutase and Prediction of Mutational Variations through in silico Methods - Nathan Vinod Kumar; Lizzy Mathew; Edward Gnanaraj Wesely (International Journal Bioautomation, 2014)
Superoxide dismutase (SOD) is one of the major enzymes expressed in the oxidative stress pathway in plants. Its expression is also evident in other taxonomic group in oxidative reactions. Pisum sativum a common plant is being studied in the present work where SOD is characterized using computational tools. SOD sequence of P. sativum [CAA42737.1] Ala and Leu rich protein with alkaline pI value was used as query sequence and used to obtain nine similar sequences through BLASTp. Phylogenetic tree was constructed using MEGA 5.0 based on neighbour joining method. Physiochemical parameters and amino acid composition was studied and compared with query sequences and other similar sequences. Secondary structures were predicted to understand the dominant components. Homology modeling of P. sativum SOD was done using SWISS MODEL and quality was evaluated using standard methods. 27 active sites were detected in SOD predicted model which were Lys rich.